The effect of crystal structure of SiO2 on the wettability of AgCuTiSiO2f/SiO2 system. (November 2018) - Ma, Q.; Li, Z.R.; Niu, H.W.; Wang, Z.Y.; Ba, J.; Qi, J.L.; Feng, J.C.; He, P.; Ma, J.
Abstract: Fused silica was root cause of poor wettability of SiO2f /SiO2 . SiO2f /SiO2 was composed of SiO2 in different states, which mean crystallized SiO2 formed fused silica and amorphous SiO2 formed quartz fibers. Wetting results show with holding time increasing, wetting angle of AgCuTi-crystallized SiO2 decreased from 137° to 87°, meaning poor wettability. Besides, Ti3 O5 and Ti2 O3 particles formed. While, wetting angle of AgCuTi-amorphous SiO2 decreased from 110° to 43°, indicating good wettability. Cu3 Ti3 O reaction layer formed. Thus, the crystal structure of SiO2 determined reaction product in wetting interface, which was a dominating influence on the wettability of AgCuTiSiO2f /SiO2 system. Graphical abstract: Highlights: SiO2f /SiO2 consisted of SiO2 in two states: crystallized and amorphous. Cu3 Ti3 O reaction layer formed in AgCuTi-amorphous SiO2 wetting interface. Ti3 O5 and Ti2 O3 particles formed in AgCuTi-crystallize SiO2 wetting interface. The fused silica was the root cause of poor wettability of SiO2f /SiO2 .